2017
DOI: 10.29252/ijrm.15.11.729
|View full text |Cite
|
Sign up to set email alerts
|

Cervical gland area as an ultrasound marker for prediction of preterm delivery: A cohort study

Abstract: Background:Preterm labor is a major cause of perinatal morbidity and mortality and it might be predicted by assessing the cervical change.Objective: To assess the association between absence of cervical gland area (CGA) and spontaneous preterm labor (SPTL).Materials and Methods: This prospective cohort study was performed on 200 singleton pregnant women with a history of SPTL, second-trimester abortion in the previous pregnancy or lower abdominal pain in current pregnancy. Each patient underwent one transvagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This absence of glands may signify the beginning of the cervical ripening process [80][81][82]. In another study, 600 pregnant women were scanned at 16-19 weeks of gestation, and the CGA was detected in 77% of the women who delivered at term vs. 55% of those who did not [80].…”
Section: Cervical Gland Area (Cga)mentioning
confidence: 99%
See 1 more Smart Citation
“…This absence of glands may signify the beginning of the cervical ripening process [80][81][82]. In another study, 600 pregnant women were scanned at 16-19 weeks of gestation, and the CGA was detected in 77% of the women who delivered at term vs. 55% of those who did not [80].…”
Section: Cervical Gland Area (Cga)mentioning
confidence: 99%
“…The absence of normal mucosal glands (cervical gland area), which is demonstrated by a hyperechoic or hypoechoic segment around the cervical mucosa, has also been proposed as a predictor of a PTB [80]. In past studies, it was shown that the detection rate of the CGA decreased after 31 weeks of gestation [81].…”
Section: Cervical Gland Area (Cga)mentioning
confidence: 99%
“…In addition, the CGA disappears at the second trimester in cases of preterm delivery before 32 weeks of gestation 2 . Therefore, the absence of the CGA can be clinically useful as a sonographic marker for cervical maturation in normal pregnancy and the prediction of preterm delivery 2–8 . Previous studies have focused on the presence or absence of CGA during the progression of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Therefore, the absence of the CGA can be clinically useful as a sonographic marker for cervical maturation in normal pregnancy and the prediction of preterm delivery. [2][3][4][5][6][7][8] Previous studies have focused on the presence or absence of CGA during the progression of gestation. However, there are no studies concerning the quantitative evaluation of longitudinal changes in the CGA, such as the actual length of the sonographically described cervical gland.…”
Section: Introductionmentioning
confidence: 99%
“…However, sonographic CL has variable sensitivity for screening, and its predictive value in the general obstetric population remains suboptimal 7,9,10 . The character of the cervical canal itself, specifically the cervical gland area (CGA), has been proposed as another useful reflection of cervical function [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%